Urban road network analysis of Yenagoa, Bayelsa State Using GIS Idhoko K.E, Ndiwari, E. L., Ogeh, V. C., & Ikegbulam, S. C. (International Journal of Engineering and Computer Science, 2017)
Good road network is essential for development of cities. Roads are established over land for the passage of human being, vehicleand animal. There is need for an effective and efficient road network for easy accessibility, mobility and connectivity as it willenhance the socio-economic development of the society. The road network of Yenagoa describe how accessible one location is toothers, within the central business district and it shows the road distribution link for the interaction of man and other facilities,utilities and services. It is on this basis that this study has applied geographic information system GIS to answer basic genericquestions on how accessible one location is to another. Social survey was carried out to acquire attribute data through the use oforal questionnaire and personal observation. The geospatial datasets were georeferenced and link with attribute database using theArcGIS software. Analysis such as; spatial search for a particular road; the shortest route between two locations by applyingconcept of road network analysis was employed. The overall aim and objectives were achieved based on the spatial analysiscarried out for accessing places and facilities within the Yenagoa metropolis by ascertaining the minimum path travel, distance,time for effective emergency response services as well as solving travel salesman problem and improve the standard of life withinthe study area.